Analisis Biomekanika pada Berbagai Posisi Pengangkatan Karung Beras Menggunakan Metode REBA dan QEC - Devi, Anita Oktaviana Trisna; Sutrisno, Agung Widiyanto Fajar (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Lifting activities in rice milling businesses are still largely done manually. This was found at the Barokah Rice Mill in Pucang, Secang, Magelang. Workers lift using three lifting positions: front carry, back carry, and overhead carry. Based on the REBA analysis, the overhead carry position scored slightly safer. At the initial lifting position, all three positions scored very high. However, once the load is lifted and carried, scores begin to decline. The overhead carry position showed the largest drop in scores. The exposure level in the QEC analysis was 57%, indicating that lifting movements need to be modified.